Images of the immortal the cult of Lü Dongbin at the Palace of Eternal Joy - Katz, Paul R. 1961- (Univ. of Hawai'i Press, 1999)
Katz breaks new ground by analyzing the texts in terms of the textuality - the process by which they were produced, transmitted, and understood."--BOOK JACKET
Keywords: Lü, Dongbin <0798-08..> - Culte; Lü, Dongbin <né 798>; Lü, Dongbin <b. 798>; Lü, Dongbin -- 798-; Yongle gong (Temple : Ruicheng, Chine); Yongle gong (Longquan Cun, China); Immortels - Culte; Taoïsme; Temples - Chine; Taoism; Kult; Yongle gong